Skills, Gender, and Performance Matter when Undergraduate Business Students Choose Specialisation within Business Courses - Leiv Opstad; Torbjørn Årethun (International School for Social and Business Studies, 2020)
The purpose of this article is to explore the heterogeneity among undergraduate Norwegian business students. This is made visible by the students' choice of subjects in their third year. The chosen methodology is the ordinary least square (OLS) regression model. By using dummy variables depending on the preferred discipline, we can analyse what impact the composition of students will have on their performance in the compulsory courses during the two first years. The students who are highest ranked by letter grades tend to select further studies in finance and accounting subjects. One should be aware of this in the design of study programmes.